Persistence assessment of cyclohexyl- and norbornyl-derived ketones and their degradation products in different OECD screening tests. (July 2015) - Seyfried, M.; van Ginkel, C.G.; Boschung, A.; Miffon, F.; Fantini, P.; Tissot, E.; Baroux, L.; Merle, P.; Chaintreau, A.
Highlights: Persistence of synthetic cyclohexyl- and norbornyl-derived ketones was assessed. Test results for cyclohexyl-derived ketones approached ultimate biodegradation. Norbornyl-derived ketones yielded primarily 2-bicyclo[2.2.1]heptane carboxylic acid. Re-synthesized degradation products were biodegradable with fresh inocula. Results underline OECD screening test limitations and need for reduced stringency. Abstract: The persistence of synthetic cyclohexyl- and norbornyl-derived ketones was assessed by using OECD 301F and 301D biodegradation tests. While cyclohexyl-derived ketones either reached or came close to the pass level (60%) after 60 d, the corresponding norbornyl derivatives yielded significantly less biodegradation (<40%). By analyzing extracts at 60 d, the key degradation products of four norbornyl derivatives were identified. Consistently, 2-bicyclo[2.2.1]heptane carboxylic acid was found as a principal degradation product with minor quantities of bicyclo[2.2.1]heptan-2-one and 2-bicyclo[2.2.1]heptane acetic acid. When the three degradation products were re-synthesized and tested individually for biodegradability, the former two were found to be ultimately biodegradable after 60 d in OECD 301D tests, thus proving non-persistence. Similarly, 2-bicyclo[2.2.1]heptane acetic acid was found to be degraded significantly, albeit with long lag phases exceeding 60 d in the case of freshwater inoculum, then ultimately reaching the pass level. On the other hand, norbornyl ketones were still only partially biodegradable in the same test. We conclude that despite the potential for ultimate biodegradation of norbornyl-derived ketones, current screening tests yield an incomplete picture of their biodegradability, particularly when applying strict OECD criteria. The appearance of long lag phases when re-testing norbornyl ketone degradation products underlines the importance of extending tests to well beyond 28 and even 60 d in the case of freshwater inocula.